Body perception in women with rheumatoid arthritis in the city of Popayán-Colombia - Molano Tobar, Nancy Janneth (2017)
Objective. To inquire about the connotation of body that has women with rheumatoid arthritis and the link with the own symptomatology of the disease. Methodology. Qualitative of the phenomenological-hermeneutic type, in which techniques of in-depth interviews with field recordings and diaries were applied. Field work was performed between the first and second periods of 2015 with 17 women with a mean age of 48.07 years ± 6.29 years with Rheumatoid Arthritis, who attended three physical therapy clinics in the city of Popayán-Colombia. Results. Five categories of analysis were obtained that consisted of: a) Pain and inflammation a limitation for daily activities; B) Rheumatoid Arthritis a permanent company; C) forced changes in my lifestyle for my health; D) I accept my body as it is and with what it has; E) My deformities a social limitation. Conclusions. It was evidenced that the woman with rheumatoid arthritis of the City of Popayán-Colombia, accepts its pathological condition despite the pain and the associated inflammation, but at the same time it generates in her a struggle to stay within the normal range for the accomplishment of its daily activities , Promoting changes in their style and way of life to stabilize their illness and adequately develop their daily activities both home and work; At the same time, does not show discomfort for his body which he accepts, but he intuits disabling situations when he confronts society, which in certain circumstances undervalues and judges, with an inquisitive look.